The new law of royalties and environmental basic sanitation in Colombia (2013)
In the past, the articles 360 and 361 of the 1991’s Constitution ruled the royalty sharing, that is, the payment made by the companies to the nation because of the exploitation of non-renewable resources. Thus, municipalities, departments and maritime and fluvial ports used to receive a percentage of those payments (direct royalties).